Reduction in rat phosphatidylethanolamine binding protein-1 (PEBP1) after chronic corticosterone treatment may be paralleled by cognitive impairment: a first study - Feldmann, Robert Enrico; Maurer, Martin H.; Hunzinger, Christian; Lewicka, Sabina; Bürgers, Heinrich; Kalenka, Armin; Hinkelbein, Jochen; Brömme, Jens O.; Seidler, Günter H.; Martin, Eike; Plaschke, Konstanze (Stress, 2008)
Chronic stress is associated with hippocampal atrophy and cognitive dysfunction. This study investigates how long-lasting administration of corticosterone as a mimic of experimentally induced stress affects psychometric performance and the expression of the phosphatidylethanolamine binding protein (PEBP1) in the adult hippocampus of one-year-old male rats. Psychometric investigations were conducted in rats before and after corticosterone treatment using a holeboard test system. Rats were randomly attributed to 2 groups (n = 7) for daily subcutaneous injection of either 26.8 mg/kg body weight corticosterone or sesame oil (vehicle control). Treatment was continued for 60 days, followed by cognitive retesting in the holeboard system. For protein analysis, the hippocampal proteome was separated by 2D electrophoresis (2DE) followed by image processing, statistical analysis, protein identification via peptide mass fingerprinting and gel matching and subsequent functional network mapping and molecular pathway analysis. Differential expression of PEBP1 was additionally quantified by Western blot analysis. Results show that chronic corticosterone significantly decreased rat hippocampal PEBP1 expression and induced a working and reference memory dysfunction. From this, we derive the preliminary hypothesis that PEBP1 may be a novel molecular mediator influencing cognitive integrity during chronic corticosterone exposure in rat hippocampus.
Gesehen am 22.04.2024